2004
DOI: 10.1097/01.jom.0000126022.25149.bf
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Body Mass Index and Physical Activity to Health Care Costs Among Employees

Abstract: This study examined the relationship between physical activity and health care costs by different weight groups. The study sample consisted of 23,490 active employees grouped into normal weight, overweight, and obese categories. After adjustment for covariates, physically moderately active (1 to 2 times/week) and very active (3 + times/week) employees had approximately $250 less paid health care costs annually than sedentary employees (0 time/week) across all weight categories. The difference was approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 21 publications
4
63
0
3
Order By: Relevance
“…12,13,16,17 As expected, costs increased with decreasing activity and increasing BMI. Estimates of increased health care costs for combined categories of PA and BMI have not, however, been previously explored in a large, population-based cohort of women.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…12,13,16,17 As expected, costs increased with decreasing activity and increasing BMI. Estimates of increased health care costs for combined categories of PA and BMI have not, however, been previously explored in a large, population-based cohort of women.…”
Section: Discussionmentioning
confidence: 64%
“…17 In this Australian study, we found differences in costs of the order of 19% between obese inactive mid-age women and obese women reporting even low levels of PA. Not surprisingly, a much greater difference (43%) was evident between sedentary obese and moderately active healthy-weight women. The Medicare costs reported here (an average of $536 per woman per year) include only the costs of visits to general practitioners, medical specialists and out-patient pathology and radiology services.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations